2016
DOI: 10.1111/omi.12150
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus mutans copper chaperone, CopZ, is critical for biofilm formation and competitiveness

Abstract: SUMMARY The oral cavity is a dynamic environment characterized by hundreds of bacterial species, saliva, and an influx of nutrients and metal ions such as copper. While there is a physiologic level of copper in the saliva, the oral cavity is often challenged with an influx of copper ions. At high concentrations copper is toxic and must therefore be strictly regulated by pathogens in order to persist and cause disease. The cariogenic pathogen Streptococcus mutans manages excess copper using the copYAZ operon th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…The biofilms were gently washed three times with PBS to remove any unattached cells and stained with calcofluor white (Sigma‐Aldrich, St. Louis, MO) to label C. albicans . Biofilms were grown with either 1 μmol L −1 dextran‐conjugated pHRodo red or dextran‐conjugated Cascade Blue (Molecular Probes, Invitrogen, Carlsbad, CA) to monitor pH changes or glucan production, respectively . The stained biofilms were examined using fluorescence microscopy and CLSM as reported .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biofilms were gently washed three times with PBS to remove any unattached cells and stained with calcofluor white (Sigma‐Aldrich, St. Louis, MO) to label C. albicans . Biofilms were grown with either 1 μmol L −1 dextran‐conjugated pHRodo red or dextran‐conjugated Cascade Blue (Molecular Probes, Invitrogen, Carlsbad, CA) to monitor pH changes or glucan production, respectively . The stained biofilms were examined using fluorescence microscopy and CLSM as reported .…”
Section: Methodsmentioning
confidence: 99%
“…Biofilms were grown with either 1 μmol L −1 dextranconjugated pHRodo red or dextran-conjugated Cascade Blue (Molecular Probes, Invitrogen, Carlsbad, CA) to monitor pH changes or glucan production, respectively. 21 The stained biofilms were examined using fluorescence microscopy and CLSM as reported. 22 Three independent experiments were performed, and the images displayed are representative of all studies.…”
Section: Fluorescence Microscopy and Confocal Laser Scanning Microsmentioning
confidence: 99%
“…The species studied included a key species for the maintenance of biofilm ecological balance that can also be present in incipient or radicular caries (A. naeslundii) and Streptococcus mutans, considered one of the most important cariogenic species [20][21][22][23][24]. The results of the present study showed that interactions between S. mutans and A. naeslundii occur during early stages of biofilm formation, leading to a decrease in lactic acid production and to a higher resistance of S. mutans to chlorhexidine exposure.…”
Section: Discussionmentioning
confidence: 62%
“…Substantial efforts have been dedicated to understanding S. mutans virulence factors [20][21][22][23] because this species is strongly associated with dental caries [24]. However, with the deeper understanding of microbial physiology within biofilms, the importance of bacterial interaction for dental biofilm cariogenicity has been recognized.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with the present study, other researchers (18) found that not all the isolates transmitted from mothers to their respective children carry the mutAI gene. It is necessary to consider that the transmission of S. mutans is a process influenced not only by microbial factors but also by host and environmental factors, which modulate host immune defenses and bacterial competitiveness (21). In addition to the salivary level of S. mutans (22), transmission fidelity has been associated with the type of delivery (18), the duration and intensity of breastfeeding (23) and the race of the host (24).…”
Section: Discussionmentioning
confidence: 99%